Pengaruh Brand Image, Product Knowledge, dan Harga Terhadap Keputusan Pembelian Produk Pakaian Fashion Bangkok pada Store Fashion Bangkok 88 - Vina Ainun Jariyah; Eko Agus Alfianto; Miftahul Huda; Any Urwatul Wusko (Economic Reviews Journal, 2024)
The Influence of Brand Image, Product Knowledge, and Price on Purchasing Decisions of Bangkok Fashion Clothing Products, This type of research is a quantitative approach. The data collection technique used is a questionnaire distributed offline. The sample used in the study was 116 respondents with probability sampling and nonprobability sampling methods, and statistical analysis such as multiple linear regression. Based on the results of this study, it can be seen that Brand Image has a positive and significant effect on purchasing decisions, Product Knowledge has a positive and significant effect on purchasing decisions, Price has a positive and significant effect on purchasing decisions, Brand Image, Product Knowledge, and Price have a positive and significant effect on purchasing decisions.